Case report: Dendritic cell-cytokine induced killer cell therapy in subjects with chronic lymphocytic leukemia and peritoneal cancer - Mehling, Brian; Wu, DongCheng; O’Gorman, Ellen; Sheridan, Daniel; Santora, Doreen; Mihályová, Renata (Frontiers in Medicine, 2023)
This study aimed to characterize the safety and efficacy of DC-CIK therapy in two patients with previously treated chronic lymphocytic leukemia or peritoneal cancer, respectively. Participants had received conventional chemotherapy treatment for their specific cancers, and in addition, 1–2 treatments of DC-CIK therapy were administered to subjects over the course of 1 year. Subject A received an initial dosage of 3 intravenous infusions of DC-CIK therapy on three successive days and a repeat dosage 6 months later. Subject B received an initial dosage of 3 intravenous infusions of DC-CIK therapy on three successive days and received further chemotherapy after approximately 1 year. No treatment-related adverse events were reported, and both patients experienced favorable outcomes from the treatment, including enhanced treatment response, increased chemotherapy tolerance, and prolonged survival in comparison to typical 5-year survival rates.